POTRET KERUKUNAN BERBASIS KEARIFAN LOKAL: IMPLEMENTASI NILAI-NILAI HARMONI DALAM UNGKAPAN“RAMPAK NAONG BRINGEN KORONG” DALAM KEHIDUPAN MASYARAKAT MADURA - Mohammad Takdir (Khazanah: Jurnal Studi Islam dan Humaniora, 2018)
This research aims to reveal the indigenous wisdom of Madurese community in building harmony and peace. This research used a new paradigm in changing negative perseptions about Madurese through the implementasion of the expression “rampak naong bringen korong” in the life behavior. This research used a field study on the meaning of harmony that applied by the people of Pamekasan Madura in the expression “rampak naong bringen korong” as local wisdom values.  This research showed that local wisdom values is reflected in the phrase known“rampak naong bringen korong” as one of the symbol in building harmony and peace with the others. The phrase “rampak naong bringin korong” is a meaningful philosophy of life, that Madura people are very fond of a harmonious, peaceful, and balance in all aspects of life. The philosophy of life reflected in the phrase becomes an anti-thesis and a denial to the stereotype of the Madurese character who is considered to be very close to violence. The form of implementation of harmony values in the expression “rampak naong bringin korong” is to invite the young generation to make life peaceful and harmonious as a symbol of unity and brotherhood.